국내 종합병원의 에너지 사용량에 영향을 미치는 요인 도출 - 정다운; 김선숙; 김혜기; 권순정 (의료·복지 건축, 2020)
Purpose : The purpose of this study is to analyze the elements that affect the energy consumption of general hospitals in Korea. Methods : Factors affecting energy consumption in general hospitals include facility elements and operating elements. The effects of these elements on energy consumption of general hospitals were analyzed by statistical methods such as t-test, anova, correlation analysis, and regression analysis. Results : Total floor area, number of operating rooms, number of MRI, number of staffs, and number of outpatients can be said as useful variables that can explain energy consumption in general hospitals. Implication : It is possible to save energy consumption in general hospitals by adjusting major variables that affect the energy consumption of general hospitals.
Keywords: 종합병원; 에너지 사용량; 병원의 운영요소; 병원의 시설요소; General Hospital; Energy Consumption; Facility elements of general hospital; Operational elements of general hospital